Measuring multidimensional deprivations and living conditions based on survey data - Oxford Poverty & Human Development Initiative (OPHI) (Oxford Poverty & Human Development Initiative (OPHI), 2012)
Briefing note on the benefits of taking a multidimensional approach to measuring deprivations and living conditions, including the added insights can arise from multidimensional measures, and how such measures are being generated at the national level. This briefing was prepared for the UN Statistical Commission meetings in February 2012.